Strategi Kepemimpinan Kepala Sekolah untuk Kinerja Guru IPA Melalui Motivasi Guru SMP Kota Lubuklinggau - Kartika Kartika; Rudi Erwandi; Wahidin (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to analyze the principal’s leadership strategies in improving science teacher performance through teacher work motivation in private junior high schools in Lubuklinggau City. The method used was a qualitative approach with a case study design. The research subjects consisted of principals and science teachers in four private junior high schools in Lubuklinggau City. Data were collected through in-depth interviews, observation, and documentation. The results indicate that the principal’s leadership strategies, including planning, organizing, actuating, and controlling, play a role in enhancing science teachers’ work motivation. Teacher work motivation functions as a mediating variable that strengthens the influence of principal leadership on science teacher performance. In conclusion, effective and consistent principal leadership is able to optimally improve science teacher performance through strengthening work motivation. Keywords: Principal Leadership, Private Junior High School, Science Teacher Performance, Teacher Motivation